Full employment: Are we there yet? - Flavia Dantas; L. Randall Wray (Levy Economics Institute of Bard College, 2017)
Flavia Dantas and L. Randall Wray argue that the emerging conventional wisdom - that the US economy has reached full employment - is flawed. The unemployment rate is not providing an accurate picture of the health of the labor market, and the common narrative attributing shrinking labor force engagement to aging demographics is overstated. Instead, falling prime-age participation rates are the symptom of a structural inadequacy of aggregate demand - a problem of insufficient job creation and stagnant incomes that conventional public policy remedies have been unable to address. The solution to our long-running secular stagnation requires targeted, direct job creation for those at the bottom of the income scale.
Keywords: 330